Research on tubular joints at Nanyang Technological University - Lie, S. T. (2014)
Presented herein is a review of the research programmes and findings on the fatigue performances of tubular joints. The studies, conducted at the Nanyang Technological University, embraced a number of welded tubular joints types that have been used in both onshore and offshore structures. Research efforts also focussed on the development of research methodologies, new modelling and assessment tools that are applicable to different types of commonly used tubular joints. Based on the key results obtained from the studies, those parameters that critically affect the fatigue performance of tubular joints are identified. In addition, some potential areas for further extensions of the presented works are suggested.